Reestruturação da disciplina "Física I" do Curso de Tecnólogo em Gerência de Obras de Edificações do CEFET/PB - Nobre, Francisco de Assis Fernandes (2006)
The aim of the present paper is to reorganize a discipline on technological physics so that the construction site of civil engineering becomes a natural environment of learning, providing the learner with the association between theory and practice as well as allowing the subject to process, in real time, information generated from his cognitive constructions and his contextualizations. Thus, a sequence of actions was taken into account: firstly, the programme was developed in the classroom, sharing with its contextualized information through experiments done under supervision by the learners in laboratories; secondly, the data which associate physics with construction were collected and, to do so, technical visits to construction sites were realized, providing the learner the association between the theory and the practice in a suitable site to the constructivist approach. As a result, the first discipline on physics of the Curso de Tecnólogos em Gerência de Obras de Edificações do CEFET/PB was re-structured in terms of syllabus, methodology, application and evaluation. In fact, this work deals with a dynamic process that gathers and gives emphasis to teaching, learning, technology, information, creativity, competence and abilities in a constructivist learning process and, as a consequence, having allowed institutional engagement